Low stress high coaxial vacuum step by step cementing method for injection molded lenses and glass lenses

CN122896435APending Publication Date: 2026-10-13NANYANG LIANYI PHOTOELECTRIC CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611092243.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-22
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0004]但是,现有技术进行塑料与玻璃的界面粘接时存在粘接强度不足,点胶易留存气泡,光学散射损耗高,且胶层残余应力大,高低温循环易脱胶,严重影响注塑镜片与玻璃镜片的胶合效果和成品镜片的质量

Benefits of technology

[0005]本发明所要解决的技术问题是如何提升注塑镜片与玻璃镜片的胶合效果,保证成品镜片的质量,针对现有技术的不足,提供一种注塑镜片与玻璃镜片的低应力高同轴真空分步胶合方法。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122896435A_ABST
    Figure CN122896435A_ABST
Patent Text Reader

Abstract

The application provides a low-stress high-coaxial vacuum step-by-step gluing method for injection-molded lenses and glass lenses, and belongs to the technical field of lens gluing. In the application, the gluing surfaces of the glass and the injection-molded lenses are modified by differential plasma respectively, the glass is coated with silane coupling agent and then is kept at constant temperature to realize the activation of the heterogeneous substrates, to improve the bonding strength by chemical bonds, and to protect the optical surface of the injection-molded lenses; then, the glass edge is ring dispensing and the center is left blank, vacuum standing is performed to eliminate bubble scattering defects; then, the whole process is vacuum alignment and lamination, and only the edge UV pre-gel is locked coaxial to prevent the eccentricity and overflow of the glue spreading; then, two-stage gradient pressure is adopted, low-pressure glue pushing is performed to fill the gap, and high-pressure setting is performed to avoid the depression of the injection-molded lenses under pressure; finally, the center light source is gradiently powered to step-by-step solidify, vacuum locking is performed, high-temperature aging is performed to release the thermal expansion mismatch stress, stress release secondary deviation is avoided, the gluing effect of the injection-molded lenses and the glass lenses is improved, and the quality of the finished lenses is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of lens bonding technology, specifically relating to a low-stress, high-coaxial vacuum stepwise bonding method for injection-molded lenses and glass lenses. Background Technology

[0002] With the miniaturization of optical communication devices, composite lenses consisting of injection-molded lenses and optical glass lenses have become the core structure of optical fiber collimation and coupling elements. The two are bonded together by optical adhesive to achieve both lightweight and high laser tolerance. The bonding process directly determines the lens's coaxial accuracy, coupling loss, and wide-temperature operating reliability.

[0003] Referring to the technical solution disclosed in Chinese Invention Patent Application No. "202510342761.3", the process adopts the processing idea of ​​center dispensing, room temperature and pressure adhesive laying, low power stepwise UV curing and offline constant temperature stress relief. By controlling the constant temperature environment, manually adjusting the lens with an eccentric microscope and slowing down the curing, the deformation problem of pure glass concave and convex lenses is improved to a certain extent. It is suitable for processing traditional achromatic optical lenses.

[0004] However, existing technologies for bonding plastics and glass interfaces suffer from insufficient bonding strength, easy retention of air bubbles in the adhesive, high optical scattering loss, large residual stress in the adhesive layer, and easy delamination during high and low temperature cycling, which seriously affect the bonding effect between injection-molded lenses and glass lenses and the quality of finished lenses. Summary of the Invention

[0005] The technical problem to be solved by this invention is how to improve the bonding effect between injection-molded lenses and glass lenses and ensure the quality of finished lenses. In view of the shortcomings of the prior art, this invention provides a low-stress, high-coaxial vacuum stepwise bonding method for injection-molded lenses and glass lenses.

[0006] To solve the above-mentioned technical problems, the technical solution adopted by the present invention is as follows: This invention provides a low-stress, high-coaxial vacuum stepwise bonding method for injection-molded lenses and glass lenses, comprising: S1. Select a plasma gas source to perform differentiated treatment on the bonding surfaces of the glass lens and the injection-molded lens respectively. Apply a silane coupling agent coating evenly to the bonding surface of the treated glass lens and let the glass lens and the injection-molded lens stand at a preset low temperature for a first preset time. S2. A pre-defined thickness of UV optical adhesive is uniformly applied along the boundary of the adhesive surface of the glass lens to form an annular adhesive channel. The space where the glass lens is located after the adhesive application is completed is evacuated, and the glass lens is left to stand for a second pre-defined time while maintaining a pre-defined vacuum level. S3. Align the glass lens and the injection-molded lens in a vacuum environment, keep them relatively stationary after the bonding surface of the injection-molded lens comes into contact with the annular adhesive channel, and irradiate the surrounding annular adhesive channel in a directional manner using an annular UV light source. S4. In the vacuum environment, the glass lens and the injection-molded lens are first squeezed together by a preset low pressure holding pressure until the UV optical adhesive in the annular adhesive channel flows and fills the adhesive gap, and then the relative static pressure is maintained by a preset high pressure holding pressure. S5. Irradiate the glass lens and the injection-molded lens with a central UV light source perpendicular to the center of the lens in a continuously gradient power manner, and simultaneously place the glass lens and the injection-molded lens at a preset high temperature for a third preset time to obtain a composite lens.

[0007] Compared with the prior art, the beneficial effects of this invention include: First, by using differentiated plasma gas sources to modify the bonding surfaces of glass and injection-molded lenses respectively, and by additionally coating the glass side with a silane coupling agent, followed by uniform constant-temperature static treatment to eliminate temperature differences and internal stress in the substrate, this setup can simultaneously complete the surface activation of two heterogeneous substrates: inorganic glass and organic injection-molded polymer. The silane coupling agent establishes a chemical bond transition layer between the glass and the subsequently coated UV adhesive. The differentiated plasma parameters can avoid corrosion of the optical curved surface of the injection-molded lens, effectively solving the problems of large surface energy differences between glass and plastic and adhesive adhesion. The problems of poor wetting and low bonding strength provide a foundation for interfacial bonding in long-term high and low temperature cycling. Based on this, a closed-loop UV adhesive is applied only to the edge of the glass lens, leaving the center blank. After completion, a high vacuum is applied in a sealed chamber for static degassing. The pre-reserved channel in the center of the loop allows microbubbles within the adhesive to completely precipitate out, solving the defects of conventional full-area dispensing where bubbles cannot escape and optical scattering loss occurs after curing, ensuring uniform light transmission and no voids in the adhesive layer. Next, after the ring-shaped UV adhesive is applied, the two lenses are aligned and bonded under constant vacuum. The edge annular adhesive channel is partially pre-irradiated with UV light. This allows the edge adhesive to lightly gel and lock the relative positions of the two lenses, while the central adhesive remains in a flowable liquid state. This effectively solves the problems of lens eccentricity, adhesive overflow, and loss of coaxiality control during the lamination and adhesive application process. Then, the lens is squeezed with two stages of gradient pressure. The low pressure slowly pushes the edge annular liquid UV adhesive to spread evenly from the outer ring towards the center of the lens, filling all the bonding gaps. The high pressure is maintained at a constant pressure to stabilize the adhesive layer thickness. This pressure is used to achieve uniform filling of the adhesive layer throughout the entire area, avoiding the pitting and uneven adhesive layer thickness that can occur with injection-molded soft lenses caused by a single high-pressure extrusion. Unevenness defects; finally, the adhesive layer cross-linking and curing is completed from the outside to the inside by using a continuous gradient power increase mode through the central UV light source. After curing, vacuum locking and high temperature isothermal aging fully release the residual stress at the interface. Step-by-step curing slows down the shear stress caused by the mismatch between injection molding and glass CTE. High temperature vacuum locking and shaping prevents secondary displacement of the lens during stress relaxation, ensuring bonding stability. Finally, a low residual stress, high coaxiality and high reliability optical communication composite lens is obtained, which effectively solves the problems of stress concentration, high and low temperature debonding and batch coupling loss dispersion in traditional one-time full-domain curing.

[0008] Optionally, the plasma source includes argon gas; when processing the glass lens, the light-transmitting area of ​​the bonding surface of the glass lens is cleaned for 40-60 seconds using the plasma source with a power of standard plasma power; when processing the injection-molded lens, the bonding surface of the injection-molded lens is impact-activated for 20-40 seconds using the plasma source with a power of 35%-45% of standard plasma power.

[0009] Optionally, the preset low-temperature environment temperature is 25±0.5℃, and the first preset time is 8~12min.

[0010] Optionally, the thickness of the annular adhesive channel is 5~15μm, the preset vacuum degree is -0.090~-0.095MPa, and the second preset time is 3~8min.

[0011] Optionally, the irradiation intensity of the annular UV light source is 300~500mW / cm². 2 The duration of a single irradiation is 2-5 seconds.

[0012] Optionally, the preset low-pressure holding pressure is 0.01~0.03MPa, and the holding time is 3~8s.

[0013] Optionally, the preset high-pressure holding pressure is 0.05~0.1MPa.

[0014] Optionally, the step S5 of irradiating the glass lens and the injection-molded lens with a central UV light source perpendicular to the center of the lens and in a continuously gradient power increase manner includes: S51. Irradiate the glass lens and the injection-molded lens with a first light power through the central UV light source, and maintain for a first curing time; S52. The illumination power of the central UV light source is increased at a constant speed from the first illumination power to the second illumination power, and maintained for the second curing time.

[0015] Optionally, the first illuminance is 200~300mW / cm². 2 The first curing time is 20~40s, and the second light irradiation power is 400~450mW / cm². 2 The second curing time is 120~240s.

[0016] Optionally, the preset high-temperature environment temperature is 55~60℃, and the second preset time is 1.5~2.5h. Attached Figure Description

[0017] The present invention will now be described in further detail with reference to the accompanying drawings.

[0018] Figure 1 This is a schematic diagram of the low-stress, high-coaxial vacuum stepwise bonding method for injection-molded lenses and glass lenses in an embodiment of the present invention. Detailed Implementation

[0019] To better understand the present invention, the following embodiments further illustrate the content of the invention, but the scope of protection of the present invention is not limited to the following embodiments. Numerous specific details are set forth in the following description to provide a more thorough understanding of the invention. However, it will be apparent to those skilled in the art that the present invention can be practiced without one or more of these details.

[0020] The term "comprising" and its variations as used herein are open-ended, meaning "including but not limited to"; the term "based on" means "at least partially based on"; the term "one embodiment" means "at least one embodiment"; the term "another embodiment" means "at least one additional embodiment"; the term "some embodiments" means "at least some embodiments"; and the term "optionally" means "optional embodiments". Definitions of other terms will be given in the following description. It should be noted that the concepts of "first," "second," etc., mentioned in this invention are used only to distinguish different devices, modules, or units, and are not intended to limit the order of functions performed by these devices, modules, or units or their interdependencies.

[0021] It should be noted that the terms "one" and "more" used in this invention are illustrative rather than restrictive. Those skilled in the art should understand that, unless otherwise expressly indicated in the context, they should be understood as "one or more".

[0022] An embodiment of the present invention provides a low-stress, high-coaxial, vacuum stepwise bonding method for injection-molded lenses and glass lenses, comprising: S1, using a plasma gas source to perform differentiated treatment on the bonding surfaces of the glass lens and the injection-molded lens respectively, uniformly coating the bonding surface of the treated glass lens with a silane coupling agent coating, and simultaneously placing the glass lens and the injection-molded lens at a preset low temperature for a first preset time; S2, uniformly applying a preset thickness of UV optical adhesive along the boundary of the bonding surface of the glass lens to form an annular adhesive channel, evacuating the space where the dispensed glass lens is located, and maintaining a preset vacuum level for a second preset time; S3, bonding the glass lens and the injection-molded lens together... The glass lens is aligned and brought closer together in a vacuum environment. After the bonding surface of the injection-molded lens comes into contact with the annular adhesive channel, it remains relatively still. The annular adhesive channel is irradiated directionally by an annular UV light source. S4. In a vacuum environment, the glass lens and the injection-molded lens are first squeezed together with a preset low pressure until the UV optical adhesive in the annular adhesive channel flows and fills the bonding gap. Then, the relative stillness is maintained by a preset high pressure. S5. The glass lens and the injection-molded lens are irradiated with a continuous gradient power by a central UV light source perpendicular to the center of the lens. The glass lens and the injection-molded lens are then left to stand at a preset high temperature for a third preset time to obtain a composite lens.

[0023] Specifically, the plasma source is argon gas. Argon plasma leaves no chemical impurities and achieves surface cleaning and micro-etching solely through ion physical bombardment, without contaminating the optical transmission surface. The silane coupling agent is an epoxy-based silane coupling agent. One end of the epoxy-based silane coupling agent condenses with the glass hydroxyl groups to form a Si-O-Si covalent bond, while the other end crosslinks with the epoxy groups of the UV adhesive to form a flexible stress buffer transition layer. The UV optical adhesive is a low birefringence UV adhesive adapted for the 1310 / 1550nm optical communication band. The dedicated optical communication UV adhesive has extremely low birefringence, avoiding interference with fiber optic coupling signals after bonding. The injection-molded lens substrate is COC / COP / PC, and the glass lens is quartz / lanthanide optical glass. Both substrates are compatible with mainstream optical communication lenses, facilitating standardized mass production process adaptation.

[0024] In this embodiment, firstly, as... Figure 1 As shown in S1, differentiated plasma gas sources are used to modify the bonding surfaces of glass and injection-molded lenses respectively. A silane coupling agent is additionally coated on the glass side, followed by uniform constant-temperature static treatment to eliminate temperature differences and internal stress in the substrate. This setup allows for simultaneous surface activation of two heterogeneous substrates: inorganic glass and organic injection-molded polymer. The silane coupling agent establishes a chemical bond transition layer between the glass and the subsequently coated UV adhesive. The differentiated plasma parameters prevent corrosion of the optical curved surfaces of the injection-molded lens, effectively solving the problems of large surface energy differences between glass and plastic, poor adhesive wetting, and low bonding strength, providing a foundation for interfacial bonding in long-term high and low temperature cycling. Based on this, as... Figure 1 As shown in S2, a closed-loop UV adhesive is applied only to the edge of the glass lens, leaving the center blank. After completion, a high vacuum is applied to the sealed cavity for static degassing. The pre-reserved channel in the center of the loop allows microbubbles within the adhesive to completely precipitate out along the central channel, solving the defects of conventional full-area dispensing where bubbles cannot escape and optical scattering loss occurs after curing, ensuring uniform light transmission and no voids in the adhesive layer; then, as... Figure 1 As shown in S3, after the annular UV adhesive coating is completed, a vacuum environment is maintained throughout the process to align and bond the two lenses. Only the edge annular adhesive channel is locally pre-irradiated with UV light. At this time, the edge adhesive can be slightly gelled to lock the relative position of the two lenses, while the central adhesive remains in a flowable liquid state, effectively solving the problems of lens eccentricity, adhesive overflow, and loss of coaxiality control during the lamination and adhesive application process; then, as... Figure 1 As shown in S4, the lens is extruded using a two-stage gradient pressure. Low pressure slowly pushes the lens, causing the edge-ring liquid UV adhesive to spread evenly from the outer edge towards the center, filling all bonding gaps. High pressure maintains a constant pressure to stabilize the adhesive layer thickness. This pressure ensures uniform filling of the adhesive layer across the entire surface, avoiding defects such as indentation and uneven adhesive layer thickness in injection-molded soft lenses caused by single-stage high-pressure extrusion. Finally, as... Figure 1As shown in S5, the adhesive layer crosslinking and curing is completed from the outside to the inside using a continuous gradient power increase mode through the central UV light source. After curing, vacuum locking and high-temperature isothermal aging fully release the residual stress at the interface. Step-by-step curing slows down the shear stress caused by the mismatch between injection molding and glass CTE. High-temperature vacuum locking and shaping prevents secondary displacement of the lens during the stress relaxation process, ensuring bonding stability. Finally, a low residual stress, high coaxiality and high reliability optical communication composite lens is obtained, which effectively solves the problems of stress concentration, high and low temperature debonding and batch coupling loss dispersion in traditional one-time full-domain curing.

[0025] Optionally, the plasma source includes argon gas; when processing glass lenses, the light-transmitting area of ​​the cemented surface of the glass lens is cleaned for 40-60 seconds using a plasma source with a power of standard plasma power; when processing injection-molded lenses, the cemented surface of the injection-molded lens is impact-activated for 20-40 seconds using a plasma source with a power of 35%-45% of standard plasma power.

[0026] Specifically, the standard plasma power is 300W, suitable for optical glass cleaning needs; the glass processing time can be selected as 40s, 50s or 60s; the injection molded lens processing power can be selected as 35% (105W), 40% (120W) or 45% (135W) of the standard power; the injection molding processing time can be selected as 20s, 30s or 40s.

[0027] In this optional embodiment, in the specific settings of S1, firstly, argon gas is uniformly selected as the plasma gas source. Argon gas is an inert gas, and the treatment process produces no oxidation byproducts and no carbon residue, thus avoiding yellowing of the lens optical surface and a decrease in light transmittance, solving the problem of oxygen / air plasma oxidation and corrosion of the lens surface. Based on this, the glass lens undergoes full-power plasma cleaning for 40-60 seconds. High-energy argon ions thoroughly remove mold release agent, oil, and micron-sized dust from the glass surface, breaking the surface Si-O bonds to generate a large number of hydroxyl active sites, providing sufficient chemical bonding sites for subsequent silane coupling agents. If the treatment time is less than 40 seconds, the removal of contaminants from the glass surface is incomplete, and the hydroxyl groups... Insufficient plasma concentration leads to a significant decrease in silane bonding strength, and exceeding 60 seconds can cause micro-etching damage to the glass edges, affecting optical profile accuracy. Subsequently, injection-molded lenses utilize low power (35%–45% of standard power) and short micro-etching activation (20–40 seconds). Low-energy argon ions generate nanoscale concave-convex microstructures only on the polymer surface, forming mechanically interlocking anchoring points, while introducing hydroxyl and carbonyl polar groups to enhance adhesive wettability. Conversely, power above 45% and activation time exceeding 40 seconds can penetrate the optical surface of the injection-molded lens, causing fogging and concave deformation, while power below 35% and activation time less than 20 seconds cannot form an effective micro-rough structure, resulting in adhesive shrinkage and weak adhesion. This setup, by differentiating plasma power and activation time to suit both inorganic hard glass and organic soft injection-molded parts, balances surface activation effect with optical surface integrity, resolving the contradiction of either poor adhesion or lens failure with uniform plasma parameters, ensuring bonding stability and lens quality.

[0028] Optionally, the preset low-temperature ambient temperature is 25±0.5℃, and the first preset time is 8~12min.

[0029] Specifically, the preset low-temperature environment temperature can be selected as 24.5℃, 25℃, or 25.5℃; the first preset settling time can be selected as 8min, 10min, or 12min. The narrow temperature range ensures lens size stability, and the settling time covers short / medium / long process cycles, adapting to different production line speeds and balancing production efficiency with interface modification stability.

[0030] In this optional embodiment, in the specific settings of S1, firstly, the settling temperature is strictly controlled at 25±0.5℃, matching the standard constant temperature reference of optical lenses in the workshop, eliminating the temperature difference between the glass and the injection-molded lens after plasma treatment, and avoiding changes in UV adhesive viscosity and uneven spreading caused by temperature difference. Conversely, temperature fluctuations exceeding ±0.5℃ will cause slight deformation of the injection-molded lens due to thermal expansion and contraction, resulting in a decrease in subsequent alignment and coaxiality accuracy. Based on this, in S1, a constant temperature settling time of 8~12min is set. On the one hand, this allows the silane coupling agent on the glass surface to fully hydrolyze and condense to complete the covalent bond formation. On the other hand, it relaxes the surface micro-stress generated by plasma treatment of the injection-molded lens and eliminates residual internal stress from injection molding. Conversely, if the settling time is less than 8min, the silane is not fully bonded and the internal stress of injection molding is not released, making the finished product prone to delamination and temperature-induced misalignment. If the settling time exceeds 12min, the hydroxyl groups on the glass surface adsorb moisture from the air and become deactivated, resulting in a decrease in bonding strength. This setup, through low-temperature static setting, achieves a triple effect of uniform substrate temperature, stable molding of silane chemical bonds, and release of internal stress in injection molded parts, eliminating process errors caused by pretreatment from the source and improving the bonding strength and coaxiality consistency of batch products.

[0031] Optionally, the thickness of the annular adhesive channel is 5~15μm, the preset vacuum degree is -0.090~-0.095MPa, and the second preset time is 3~8min.

[0032] Specifically, the thickness of the annular adhesive channel can be selected as 5μm, 10μm, or 15μm; the preset vacuum level can be selected as -0.090MPa, -0.092MPa, or -0.095MPa; and the second preset time can be selected as 3min, 5min, or 8min. The adhesive layer thickness covers the specifications of miniature / standard optical communication lenses, the vacuum range balances degassing effectiveness with equipment cost, and the degassing time is adaptable to UV adhesives of different viscosities, making it highly adaptable to mass production.

[0033] In this optional embodiment, in the specific settings of S2, firstly, the thickness of the annular adhesive channel is controlled at 5~15μm to match the low-loss optical index of the optical communication lens. Conversely, if the adhesive layer thickness is less than 5μm, the adhesive layer will not be fully filled after pressing and there will be local missing adhesive, resulting in increased coupling loss. If the adhesive layer thickness is greater than 15μm, the curing shrinkage will increase, the residual stress at the interface will be significantly increased, and the adhesive will easily desorb during high and low temperature cycles. At the same time, a center adhesive-free channel is reserved in the annular adhesive distribution, so that bubbles can completely escape along the center channel during vacuum degassing. On this basis, the cavity vacuum degree is maintained at a high negative pressure of -0.090~-0.095MPa. Conversely, when the negative pressure is below -0.090 MPa, residual air in the cavity cannot completely expel the microbubbles within the adhesive, resulting in scattering defects after curing. Conversely, when the negative pressure is above -0.095 MPa, approaching the ultimate vacuum, equipment energy consumption increases significantly without additional degassing gain. The second preset time, a vacuum settling and degassing period of 3-8 minutes, allows the microbubbles within the adhesive to expand and burst completely under negative pressure. Conversely, if settling for less than 3 minutes, microbubbles are not completely expelled, while if settling for more than 8 minutes, prolonged negative pressure on the UV adhesive can lead to the volatilization of small molecules, altering the adhesive's refractive index and affecting optical performance. This configuration ensures that the thickness of the annular adhesive layer is adapted to the low-loss requirements of optical communication. The high vacuum combined with sufficient settling time effectively eliminates bubble defects in the adhesive layer, solving the problems of high bubble defect rates and substandard optical performance in atmospheric pressure dispensing processes.

[0034] Optionally, the irradiation intensity of the ring-shaped UV light source is 300~500mW / cm². 2 The duration of a single irradiation is 2-5 seconds.

[0035] Specifically, the ring-shaped UV light intensity can be selected as 300mW / cm². 2 400mW / cm 2 Or 500mW / cm 2 The single pre-curing time can be selected as 2s, 3s, or 5s. The pre-curing degree can be precisely controlled by the light intensity and time range, locking the position without blocking the flow, and adapting to the pre-forming process of annular glue channels for UV adhesives of different viscosities.

[0036] In this optional embodiment, in the specific settings of S3, firstly, the irradiation intensity of the annular UV light source is 300~500mW / cm². 2 Only localized irradiation of the edge annular adhesive channel achieves mild gel pre-curing; conversely, light intensity below 300 mW / cm² is used. 2 The edge adhesive cannot form a stable gel layer, leading to relative slippage and coaxiality loss of the lens during lamination and bonding, even with light intensity exceeding 500mW / cm². 2When the edge adhesive completely cures and loses its fluidity, subsequent low-pressure adhesive application cannot fill the center, resulting in large areas of missing adhesive. Based on this, a single pre-curing irradiation time of 2-5 seconds ensures that the surface gel and interior of the adhesive channel remain liquid, preserving its inward spreading and flow capabilities. Conversely, irradiation time less than 2 seconds results in insufficient gel layer thickness and poor locking effect, while irradiation time exceeding 5 seconds causes the ring adhesive to fully cross-link and cure, blocking the adhesive's central filling channel. This setup precisely controls the edge adhesive to only undergo surface pre-gelation, locking the coaxial relative position of the two lenses while preserving the adhesive's flow and filling properties, thus addressing both the requirements of high coaxiality and complete adhesive layer filling.

[0037] Optionally, the preset low-pressure holding pressure is 0.01~0.03MPa, and the holding time is 3~8s.

[0038] Specifically, the preset low-pressure holding pressure can be selected as 0.01MPa, 0.02MPa, or 0.03MPa; the low-pressure holding time can be selected as 3s, 5s, or 8s. Among them, the low-pressure range is suitable for injection molded lenses of different thicknesses and hardnesses, and the holding time is matched with the flow rate of high and low viscosity UV adhesives, which greatly improves the consistency of adhesive layer thickness in mass production.

[0039] In this optional embodiment, in the specific settings of S4, firstly, the low-pressure holding pressure is 0.01~0.03MPa and held for 3~8s. The two lenses are gently squeezed under low pressure, and the annular liquid UV adhesive is pushed from the outer ring to the center of the lens by uniform and slow pressure, completely filling all the bonding gaps between the two lenses. Conversely, if the pressure is lower than 0.01MPa, the pushing force is insufficient, and the adhesive cannot fill the central area, resulting in a lack of adhesive in the center. If the pressure is higher than 0.03MPa, the instantaneous pressure is too large, and the optical surface of the injection-molded soft lens is deformed by pressure. At the same time, a large amount of adhesive overflows from the edge of the lens, causing poor adhesive overflow. Based on this, the 3~8s holding time is matched with the flow rate of the adhesive to ensure that the adhesive is evenly spread without local thickness differences. Conversely, if the holding pressure is less than 3s, the central area is not completely filled, and if the holding pressure exceeds 8s, the continuous low-pressure squeezing can easily cause the edge pre-gel adhesive channel to break, and the lens to shift off-center. This setup employs low-pressure, long-term, and gradual adhesive application, which is well-suited to the low hardness of injection-molded lenses. It achieves uniform filling of the adhesive layer across the entire surface without damaging the optical curvature, thus resolving lens deformation, adhesive overflow, and adhesive shortage defects caused by high-pressure one-time pressing.

[0040] Optionally, the preset high pressure holding pressure is 0.05~0.1MPa.

[0041] Specifically, the preset high-pressure holding pressure can be selected as 0.05MPa, 0.08MPa or 0.1MPa. The high-pressure range takes into account both the stability of the adhesive layer and the dimensional integrity of the injection-molded lens, and is suitable for the thickness control requirements of various specifications of composite lenses.

[0042] In this optional embodiment, in the specific settings of S4, after the adhesive is fully spread and filled under low pressure, a constant pressure of 0.05~0.1MPa is switched to. The high pressure provides stable bonding constraint, counteracting the slight rebound tendency of the adhesive under vacuum conditions and locking in the uniformity of the adhesive layer thickness. Conversely, if the high pressure is below 0.05MPa, the adhesive layer rebound causes localized thinning, leading to fluctuations in coupling loss. If the high pressure is above 0.1MPa, the continuous rigid pressure compresses the injection-molded lens, causing irreversible creep deformation and altering the lens's optical curvature. This setup ensures that the high-pressure holding process is conducted under vacuum conditions without air intrusion, resulting in a stable and controllable adhesive layer thickness. This provides a uniform adhesive layer substrate for subsequent gradient UV curing, preventing uneven adhesive layer thickness from causing disordered curing stress distribution.

[0043] Optionally, the process of irradiating the glass lens and the injection-molded lens with a continuously gradient power increase by a central UV light source perpendicular to the center of the lens in S5 includes: S51, irradiating the glass lens and the injection-molded lens with a first light power by the central UV light source and maintaining a first curing time; S52, uniformly increasing the light power of the central UV light source from the first light power to the second light power and maintaining a second curing time.

[0044] In this optional embodiment, in the specific settings of S5, firstly, a low-power central UV light source is used to slowly cure the central adhesive layer. This slow cross-linking at low power releases the initial shrinkage stress of the adhesive layer, avoiding the severe shrinkage and concentration of interfacial shear stress caused by instantaneous high-power curing. Based on this, the light power is uniformly and linearly increased to a higher intensity and cured continuously for a longer period, gradually completing the cross-linking from the semi-cured edge area towards the center, achieving gradient curing from the outside in. This progressively releases the interfacial stress caused by the mismatch in thermal expansion coefficients between the injection-molded lens and the glass lens. Unlike traditional full-area synchronous curing, step-by-step gradient curing significantly reduces residual stress and optical birefringence in the adhesive layer. This setup, with two-stage continuous power-increasing curing, eliminates light interruptions and the need for air cooling, effectively improving the curing effect by relying on the gradient curing rate to release stress.

[0045] Optionally, the first illuminance is 200~300mW / cm². 2 The first curing time is 20~40s, and the second light irradiation power is 400~450mW / cm. 2 The second curing time is 120~240s.

[0046] Specifically, the first illumination power can be selected as 200mW / cm². 2 250mW / cm 2 Or 300mW / cm 2 The first curing time can be selected as 20s, 30s, or 40s; the second light power can be selected as 400mW / cm². 2 420mW / cm 2Or 450mW / cm 2 The second curing time can be selected as 120s, 180s, or 240s. The two power levels and time ranges can cover the curing requirements of small and large lenses, balancing stress release effect and mass production efficiency.

[0047] In this optional embodiment, in the specific settings of S51 and S52, the initial first illumination power is 200~300mW / cm. 2 Furthermore, curing for 20-40 seconds, with low power and slow cross-linking in the inner region of the central adhesive layer, results in a gradual shrinkage rate of the adhesive layer, avoiding instantaneous stress concentration. Conversely, when the power is below 200mW / cm², the effect is more pronounced. 2 The curing rate is too slow, resulting in low production efficiency, while the power consumption exceeds 300mW / cm. 2 Initial shrinkage is severe, and interfacial stress increases significantly. Simultaneously, curing time less than 20 seconds results in incomplete cross-linking of the inner layer, while curing time exceeding 40 seconds leads to a longer production cycle and stress-free optimization gains. Based on this, the pressure is uniformly increased to 400~450mW / cm². 2 Continuous curing for 120~240s, high power ensures complete cross-linking of the adhesive layer, guaranteeing bond strength and temperature resistance. Conversely, power below 400mW / cm² results in poor adhesion. 2 The adhesive layer is not fully cured internally, resulting in insufficient implicit adhesion, while the power exceeds 450mW / cm. 2 The curing process is highly exothermic, widening the temperature difference between the two lenses and causing stress rebound. Furthermore, curing times of less than 120 seconds result in deep intercalation, while times exceeding 240 seconds lead to increased energy consumption and decreased efficiency. This design, with its two-stage power gradient range verified through high and low temperature cycling, reduces residual stress in the adhesive layer by over 60%, and controls the birefringence loss of the finished product to within 0.02 dB, meeting the specifications for high-speed optical communication devices.

[0048] Optionally, the preset high-temperature ambient temperature is 55~60℃, and the second preset time is 1.5~2.5h.

[0049] Specifically, the preset high-temperature aging temperature can be selected from 55℃, 58℃, or 60℃; the third preset aging time can be selected from 1.5h, 2h, or 2.5h. Among them, the aging temperature is adapted to the upper limit of heat resistance of various injection molded lenses such as COC / COP / PC, and the aging time takes into account both stress release effect and mass production capacity, and is adapted to the standardized production line of optical communication lenses.

[0050] In this optional embodiment, in the specific settings of S5, firstly, after UV curing, the cavity maintains a vacuum environment and the lens remains stationary. The temperature is then raised to 55-60℃ for constant-temperature aging. This low-temperature aging process slowly dissipates residual shear and tensile stress at the interface between the adhesive layer and the two substrates. Conversely, below 55℃, the stress relaxation rate is extremely low, resulting in poor aging. Above 60℃, the thermal expansion of the injection-molded lens intensifies, generating additional compressive stress in a static state. Based on this, a long-term vacuum-locked aging process of 1.5-2.5 hours is performed, without unlocking the lens positioning mechanism throughout. This completely avoids secondary eccentricity caused by lens slippage during the offline high-temperature baking stress release process. Conversely, if the aging time is less than 1.5 hours, residual stress release is insufficient, and high-low temperature cycles easily lead to adhesive delamination. If the time exceeds 2.5 hours, production line turnover efficiency is too low. This setup ensures that the vacuum-sealed environment simultaneously isolates moisture and dust, preventing contamination of the lens's optical surface during the aging process, guaranteeing coaxial deviation of the finished product, and allowing it to withstand multiple thermal shocks from -40℃ to 85℃ without delamination or adhesive layer cracking.

[0051] Example 1: PC injection-molded collimating lenses and quartz glass lenses were used as the processing objects. The glass lenses underwent standard power argon plasma treatment for 40 seconds, followed by coating with a silane primer and holding at a constant temperature of 25°C for 8 minutes. A 5μm thick annular UV adhesive was applied to the glass edges, and the lenses were degassed under a high vacuum of -0.090MPa for 3 minutes. Mechanical alignment and bonding were then performed in a vacuum environment at 300mW / cm². 2 Circular UV pre-curing for 2 seconds; low-pressure application at 0.01MPa for 3 seconds, followed by high-pressure setting at 0.05MPa; central light source 200mW / cm². 2 Pre-curing for 20 seconds, then uniformly increasing to 400 mW / cm² 2 The curing process lasts for 120 seconds, followed by vacuum locking and aging at 55℃ for 1.5 hours. The finished product exhibits a coaxial deviation ≤2.0μm, with no bubbles, missing adhesive, or overflow defects throughout the adhesive layer, and uniform interface bonding. After 50 cycles of high and low temperature testing from -40℃ to 85℃, the adhesive interface shows no delamination, microcracks, or delamination. The fiber optic coupling loss at 1550nm remains stable at ≤0.28dB. Compared to conventional atmospheric pressure synchronous curing processes, the residual stress at the finished product interface is reduced by more than 55%, and the yield rate for mass production is increased by 16%.

[0052] Example 2 uses a COP injection-molded collimating lens and a lanthanide optical glass lens as the processing objects. The glass lens is treated with standard power argon plasma for 50 seconds, and the injection-molded lens is treated with 40% low power plasma for 30 seconds. After coating the glass with a silane primer, it is kept at a constant temperature of 25°C for 10 minutes. A 10μm thick annular UV adhesive is applied to the glass edge, and the glass is degassed under vacuum at -0.092MPa for 5 minutes. The glass is then aligned and bonded in a vacuum environment at 400mW / cm. 2 Circular UV pre-curing for 3 seconds; low-pressure application at 0.02MPa for 5 seconds, followed by high-pressure setting at 0.08MPa; central light source 250mW / cm². 2Pre-curing for 30 seconds, then uniformly increasing to 420 mW / cm² 2 The curing process lasts for 180 seconds, followed by vacuum locking and aging at 58℃ for 2 hours. The finished product exhibits a coaxial deviation of ≤1.5μm, excellent uniformity in adhesive layer thickness, and is free of bubbles and localized thickness variations. After 50 high and low temperature cycles, the interfacial bond strength shows no attenuation and no optical birefringence drift, with stable fiber coupling loss ≤0.22dB. Compared to traditional processes, residual stress is reduced by 65%, and batch yield is improved by 20%.

[0053] Example 3: Using a COC injection-molded collimating lens and a high-transmittance quartz glass lens as the processing objects, the glass lens was subjected to standard power argon plasma treatment for 60 seconds, and the injection-molded lens was subjected to 45% low-power plasma treatment for 40 seconds. After coating the glass with a silane primer, it was kept at a constant temperature of 25°C for 12 minutes. A 15μm thick annular UV adhesive was coated on the glass edge, and degassed under a high vacuum of -0.095MPa for 8 minutes. CCD mechanical alignment and bonding were performed in a vacuum environment at 500mW / cm². 2 Circular UV pre-curing for 5 seconds; low-pressure application at 0.03 MPa for 8 seconds, followed by high-pressure setting at 0.1 MPa; central light source 300 mW / cm². 2 Pre-curing for 40 seconds, then uniformly increasing to 450 mW / cm² 2 The curing process lasts for 240 seconds, followed by vacuum locking and aging at 60℃ for 2.5 hours. The coaxial deviation of the finished product is ≤1.9μm. Even with a thick adhesive layer, the entire surface remains free of bubbles, shrinkage, and edge overflow. After 80 cycles of high and low temperature cycling from -40℃ to 85℃, the adhesive interface remains firmly bonded, without delamination or cracks. Optical loss shows no drift, and fiber optic coupling loss remains stable at ≤0.26dB. Compared to conventional thick adhesive layer curing processes, which are prone to stress cracking, warping, and loss exceeding tolerances, this invention reduces residual stress by 62% and improves yield under extreme conditions by 22%.

[0054] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A low-stress, high-coaxial vacuum stepwise bonding method for injection-molded lenses and glass lenses, characterized in that, include: S1. Select a plasma gas source to perform differentiated treatment on the bonding surfaces of the glass lens and the injection-molded lens respectively. Apply a silane coupling agent coating evenly to the bonding surface of the treated glass lens and let the glass lens and the injection-molded lens stand at a preset low temperature for a first preset time. S2. A pre-defined thickness of UV optical adhesive is uniformly applied along the boundary of the adhesive surface of the glass lens to form an annular adhesive channel. The space where the glass lens is located after the adhesive application is completed is evacuated, and the glass lens is left to stand for a second pre-defined time while maintaining a pre-defined vacuum level. S3. Align the glass lens and the injection-molded lens in a vacuum environment, keep them relatively stationary after the bonding surface of the injection-molded lens comes into contact with the annular adhesive channel, and irradiate the surrounding annular adhesive channel in a directional manner using an annular UV light source. S4. In the vacuum environment, the glass lens and the injection-molded lens are first squeezed together by a preset low pressure holding pressure until the UV optical adhesive in the annular adhesive channel flows and fills the adhesive gap, and then the relative static pressure is maintained by a preset high pressure holding pressure. S5. Irradiate the glass lens and the injection-molded lens with a central UV light source perpendicular to the center of the lens in a continuously gradient power manner, and simultaneously place the glass lens and the injection-molded lens at a preset high temperature for a third preset time to obtain a composite lens.

2. The low-stress, high-coaxial vacuum stepwise bonding method for injection-molded lenses and glass lenses as described in claim 1, characterized in that, The plasma source includes argon gas; when processing the glass lens, the light-transmitting area of ​​the cemented surface of the glass lens is cleaned for 40-60 seconds using the plasma source with a power of standard plasma power; when processing the injection-molded lens, the cemented surface of the injection-molded lens is impact-activated for 20-40 seconds using the plasma source with a power of 35%-45% of standard plasma power.

3. The low-stress, high-coaxial vacuum stepwise bonding method for injection-molded lenses and glass lenses as described in claim 2, characterized in that... The preset low-temperature environment temperature is 25±0.5℃, and the first preset time is 8~12min.

4. The low-stress, high-coaxial vacuum stepwise bonding method for injection-molded lenses and glass lenses as described in claim 1, characterized in that, The thickness of the annular adhesive channel is 5~15μm, the preset vacuum degree is -0.090~-0.095MPa, and the second preset time is 3~8min.

5. The low-stress, high-coaxial vacuum stepwise bonding method for injection-molded lenses and glass lenses as described in claim 4, characterized in that, The irradiation intensity of the ring-shaped UV light source is 300~500mW / cm². 2 The duration of a single irradiation is 2-5 seconds.

6. The low-stress, high-coaxial vacuum stepwise bonding method for injection-molded lenses and glass lenses as described in any one of claims 1 to 5, characterized in that, The preset low-pressure holding pressure is 0.01~0.03MPa, and the holding time is 3~8s.

7. The low-stress, high-coaxial vacuum stepwise bonding method for injection-molded lenses and glass lenses as described in claim 6, characterized in that, The preset high-pressure holding pressure is 0.05~0.1MPa.

8. The low-stress, high-coaxial vacuum stepwise bonding method for injection-molded lenses and glass lenses as described in any one of claims 1 to 5, characterized in that, The step S5, which involves irradiating the glass lens and the injection-molded lens with a central UV light source perpendicular to the center of the lens and using a continuous gradient power increase, includes: S51. Irradiate the glass lens and the injection-molded lens with a first light power through the central UV light source, and maintain the first curing time. S52. The illumination power of the central UV light source is increased at a constant speed from the first illumination power to the second illumination power, and maintained for the second curing time.

9. The low-stress, high-coaxial vacuum stepwise bonding method for injection-molded lenses and glass lenses as described in claim 8, characterized in that, The first illumination power is 200~300mW / cm 2 The first curing time is 20~40s, and the second light irradiation power is 400~450mW / cm². 2 The second curing time is 120~240s.

10. The low-stress, high-coaxial vacuum stepwise bonding method for injection-molded lenses and glass lenses as described in any one of claims 1 to 5, characterized in that, The preset high-temperature environment temperature is 55~60℃, and the second preset time is 1.5~2.5h.

Citation Information

Patent Citations

  • Glued lens processing technology capable of preventing deformation

    CN120652641A